A stocktaking of knowledge products on peatlands, fires and haze in Southeast Asia, 1990 to 2020 - Dermawan, A.; Brady, M.A.; Muchlish, U.; Okarda, B.; Purnomo, H.; Andrianto, A.; Komarudin, H.; Liswanti, N.; Silviana, S.H. (Center for International Forestry Research, 2022)
One key activity of MAHFSA is to stocktake existing knowledge products and develop and deploy the knowledge products related to peatlands and fires in Southeast Asia. The stocktake analysis synthesises existing knowledge products by categorising them into five thematic areas policies, tenure, economics, best practices, and monitoring. It also classified knowledge products based on geographical location, focusing on the country and regional levels. Moreover, the study categorises the knowledge products based on the elements of integrated fire management, from prevention, preparedness, suppression, and recovery. By applying text and co-occurrence analyses, the study highlights salient topics of the knowledge products related to peatlands in Southeast Asia. The result shows that thematic areas and knowledge product types vary between ASEAN member states.